IT Disaster Response Lessons Learned in the Field - Moore, Greg D. (Apress : Imprint: Apress, 2016)
Learn how to develop solutions to handle disasters both large and small. Real-world scenarios illustrate the importance of disaster response (DR) planning. Disaster Response takes a different approach to IT disaster response plans. Rather than focusing on details such as what hardware you should buy or what software you need to have in place, the book focuses on the management of a disaster and various management and communication tools you can use before and during a disaster. This book examines disasters in general-a compilation of lessons the author learned over the course of years working in IT, reviewing plane crashes, and his experiences as a cave rescuer and cave rescue instructor. Although at first it may seem that none of these are really related, the truth is they all have elements in common. In each case, the unexpected has happened. Just as not all plane crashes are deadly, not all IT mishaps have terrible consequences. With the proper training and approach, many problems can either be avoided in the first place or better handled if they do arise. The book contains practical guidance on: How to think about a disaster both before it happens and while it's happening How to apply management skills used in other fields during disasters How to get everyone on board when it comes to planning for and handling disasters How to better deal with smaller, more manageable-and more frequently occurring-disasters.